THE DISCRIMINANT OF ABELIAN NUMBER FIELDS - Interlando, J. Carmelo; Dantas Lopes, Jose Othon; Da Nobrega Neto, Trajano Pires [UNESP] (World Scientific Publ Co Pte Ltd, 2006)
A formula for computing the discriminant of any Abelian number field K is given. It is presented as a function of the conductor m of K and of the degrees of the fields K boolean AND Q(zeta(p)alpha) over Q, where p runs through the set of primes that divide m, and p(alpha) is the greatest power of p that divides m.
Keywords: Characters; conductors; cyclotomic fields; discriminants of Abelian number fields; Hasse Theorem